Research of formation of apatite-like layer on the surface of glass-ceramic coatings for dental implants - Savvova, O.V.; Fesenko, O.I.; Babich, O.V. (Functional Materials, 2018)
The prospects of application of calcium phosphate-silicate coatings on titanium alloys for dental implantology have been analyzed. The calcium silicophosphate glass was developed in the system R₂O-RO-CaF₂-R₂O₃-P₂O₅-SiO₂ and it was obtained using a scraper technology under low temperature short-term thermal treatment of glass-crystalline titanium coatings with given mechanical and thermal properties. Solubility of glass-crystalline coatings in distilled water and physiological fluids was investigated. The peculiarities of forming the apatite-like mineralized layer on the surface of calcium phosphate silicate coatings in vitro for one month, in connection with the pH of the solution and leaching of calcium and phosphate cations in distilled water, are formulated. The obtained physicochemical and microbiological data can be used for the development of bioactive glass-crystalline coatings for titanium alloys with a shorter term for resorption, for dental endoprosthetics.